How is Ambulatory Electrocardiogram Predictive of Stroke in Atrial Fibrillation Patients?. (10th October 2022) - Zhuo, Xiuping; Huang, Meinv
Abstract : Background . Atrial fibrillation (AF) is a significant stroke risk factor. Further research is needed to clarify whether higher atrial fibrillation burden (AFB) link to the elevated risk of ischemic embolism, and how AF burden could combine with CHA2 DS2 -VASc score to improve the anticoagulation strategy. We aim to evaluate if the AF burden characterized using 24-hours Holter ECG monitoring is associated with the risk of ischemic stroke. Methods . This cohort study enrolled 210 Holter ECG monitoring detected atrial fibrillation patients. The burden of atrial fibrillation was defined as the percentage of time in atrial fibrillation during the monitoring period, and the AF burden and CHA2 DS2 -VASc score were compared between patients with and without thromboembolic outcomes. Multivariate regressions were conducted to estimate the predictors of thromboembolic outcomes. Results . Eighteen thromboembolic events occurred within a median follow-up of 11.39 months. Patients with ischemic stroke had higher CHA2 DS2 -VASc scores but not higher AF burden. After adjusting for age, hypertension, diabetes, anticoagulation, antithrombotic therapy, AF burden, and AF with higher CHA2 DS2 -VASc score was associated with increased risk for ischemic stroke (hazard ratio (HR), 15.17). CHA2 DS2 -VASc score > 4.5 was a predictor of significantly higher risk of future stroke (AUC 0.92). Conclusions . In Holter ECG monitoring detected AF, AF burden does not significantly impact the subsequent risk of stroke; whereas, CHA2 DS2 -VASc scoring is still a robust predictor of stroke risk. This may illustrate that once AF is detected from Holter ECG monitoring, underlying risk factors appear to be more predictive of subsequent stroke risk than atrial fibrillation burden.